Sinergitas Prinsip Good Governance dan Kekuatan Negara: Upaya Mewujudkan Kesejahteraan Publik di Indonesia - Muchammad Daing Azimattara; Adinda Ari Wijayanti (Journal of Contemporary Law Studies, 2025)
The application of good governance principles is a crucial prerequisite for creating effective, accountable, and public interest-oriented governance. State power, on the other hand, plays a strategic role in determining the extent to which public policies can be implemented to achieve public welfare. This study aims to analyze the synergistic relationship between the concept of good governance and state power within the framework of social welfare development in Indonesia. Using a normative-juridical and conceptual approach, this study examines the principles of good governance as stipulated in various national and international legal instruments, and analyzes the role of state power in realizing a welfare state. The results of the study indicate that the relationship between good governance and state power is complementary, not contradictory. A strong state without good governance has the potential to give rise to authoritarianism, while good governance without the support of effective state power will lose the power to implement policies. Therefore, public welfare can only be achieved through a balance between state authority and good governance principles such as transparency, accountability, participation, and the rule of law. This study emphasizes the importance of strengthening state institutional capacity while instilling good governance values ​​as the foundation for equitable and sustainable national development.